A novel approach for length scale control in structural topology optimization. Issue 10 (3rd October 2019) - Gao, Jiawen; Song, Baowei; Mao, Zhaoyong
ABSTRACT: This article proposes a novel method for topology optimization with length scale control. In this method, the structural skeleton based on the level set framework is employed. On this basis, the concept of the skeleton feature is proposed. The skeleton feature is defined as a circle, of which the centre is the skeleton point and the radius is the length scale. The signed distance function based on the skeleton feature is applied to achieve minimum and maximum length scale control. The length scale constraint is determined according to the location relationship between the structure and the skeleton feature. An increasing Lagrange multiplier is applied for length scale constraints. Several simple examples are presented to demonstrate the effectiveness of the skeleton features in length scale control.